The Crime of Maritime Piracy in the 2010 Reform of the Spanish Penal Code (Spanish Yearbook of International Law, 2012)
In 2010, the Spanish Criminal Code has been reformed in order to include again the crime of maritime piracy after the recrudescence of this phenomenon in the waters of the Horn of Africa. Due to the fact that Spain is a maritime country, the internal regulation against piracy is ancient and rich. This crime was already described in the Siete Partidas (Seven-Part Code), the Castilian statutory code compiled during the reign of Alfonso X of Castile (1252–1284), and has been punish at least from 1801, by an Order of the King Carlos IV consecrated to the regulation of Privateering. Later, in the epoch of the codifĳication, it starts being included usually in the Criminal Codes, but this trend broke with the absence of Piracy in the Criminal Code of 1995, because it had stopped being frequent in practice. The historical analysis of all this regulation demonstrates that Spanish Law has always recognized the nature of crime against the law of nations of Piracy and, at the moment of typifying and punishing it, has transposed the universal competence of jurisdiction that was conferred by Public International Law. The 2010 reform consists in the introduction of two new articles in the Criminal Code: in the fĳirst place, Article 616 ter, which possesses a very wide material, spatial and personal scope, allowing to chase all kinds of acts of violence or depredation in the sea against the ships and platforms, persons or goods on board, with independence of the nationality of the authors and of the victims, of the maritime space and nationality of the craft or platform where they have been committed, or of the motivation that has stimulated the authors. With such a wide scope, the recent regulation answers correctly to the new reality of the piracy, which frequently is carried out in the territorial waters of failed States, or that is difficult to distinguish of the maritime terrorism when the pirates are nothing more than a link of a criminal chain formed with political purposes. In the second place, another article has been included, 616 quáter, which does not have very much sense regarding to the fact that it typifĳies and penalizes as piracy conducts that should be considered to be rather like constitutive of the crimes of resistance, disobedience or attempt on the authority or its agents typifĳied in other chapters of the Criminal Code.